TEACHER’S JOB SATISFACTION AND SELFEFFICACY: A REVIEW - Gkolia, Aikaterini; Belias, Dimitrios; Koustelios, Athanasios (European Scientific Journal, ESJ, 2014)
The main aim of the present study is to provide a clear picture and investigate the relation between job satisfaction and self-efficacy experienced by general employees and teachers, as it rises through literature review. There seems to be no consensus about how job satisfaction should be defined, as the definition depends on the research subject and on each individual’s priorities. During the past decades, many different theories and models of job satisfaction have been developed. In addition, different factors that are likely to have an influence on job satisfaction have been distinguished, as well as several consequences emerging from job satisfaction. In addition, the concept of self-efficacy has been defined in many different ways. In general, an educator is conceived as one of the most important persons responsible for shaping a nations’ future. The review shows that schools must pay more attention to improving teacher’s job satisfaction and self-efficacy, investigating and enhancing those factors which promote teachers’ job satisfaction and personal efficacy. Moreover, the current review provides information about instruments to measure teacher’s job satisfaction and self-efficacy. The review shows that different factors of teachers’ job satisfaction are related and have a positive influence on different factors of teachers’ efficacy. Implications and suggestions for future empirical research of findings are drawn as well.